Assessing the impact of the COVID-19 pandemic on uptake and experiences of gestational diabetes mellitus screening in Ontario: A parallel convergent mixed-methods study. - Dima Hadid; Rebecca H Correia; Sarah D McDonald; Elizabeth K Darling; David Kirkwood; Aaron Jones; Andrea Carruthers; Cassandra Kuyvenhoven; Michelle Howard; Devon Greyson; Sujane Kandasamy; Meredith Vanstone (PLoS ONE)
Objective Gestational diabetes mellitus (GDM) is a common medical complication of pregnancy that leads to adverse outcomes for both infants and pregnant people. Early detection and treatment can mitigate these negative outcomes. The COVID-19 pandemic strained healthcare and laboratory services, including GDM screening programs. Adapted GDM screening guidelines were introduced in many jurisdictions. This study examined changes in uptake, modality, and experiences of GDM screening in Ontario, Canada during the COVID-19 pandemic. Methods This convergent mixed-method study involved a population-based retrospective cohort analysis of Ontario-based health administrative data to describe and compare gestational diabetes screening rates among 85,228 individuals with live, in-hospital births between January 1-March 31 before (2019) and during the COVID-19 pandemic (2021 and 2022). Descriptive analyses were conducted for GDM screening pathways aligning with usual and pandemic-adapted screening guidance. Qualitative descriptive interviews were conducted about experiences and decision-making of GDM screening with 43 Ontario residents who gave birth between May 2020 and December 2021. Data were integrated during the design and interpretation phases. Results There were small but significant increases in GDM screening during the pandemic; likelihood of screening completion using any modality increased in 2021 and 2022 compared to 2019. Testing modality shifted; the alternate screening strategies introduced during COVID-19 were adopted by clinicians. Interview participants perceived GDM screening to be important and obligatory but accompanied by a degree of stress about potential COVID-19 exposure. Conclusion Despite health system challenges experienced in Ontario during the COVID-19 pandemic, GDM screening rates increased in the study population, demonstrating the success of adapted GDM screening guidelines. Decisions about screening modalities were driven by clinician expertise, and interview participants were satisfied to provide informed consent to these recommendations.